Membaca dialog Yesus dan Nikodemus melalui lensa persahabatan - Butarbutar, Adolf Bastian (KURIOS, 2024)
This study examines the dialogue between Jesus and Nicodemus in John 3:1-21 through the theological lens of friendship, offering a fresh perspective on this pivotal Gospel narrative. Using narrative hermeneutics in conjunction with biblical theological analysis, this research demonstrates that friendship functions not merely as an anthropological category but as a fundamental theological concept for understanding mission, soteriology, and ecclesiology. The analysis reveals that Jesus' approach to Nicodemus embodies characteristics of authentic friendship: recognition, intellectual engagement, mutual respect, and transformative commitment. Drawing on contemporary friendship theology, particularly Jürgen Moltmann's "open friendship" concept, this study shows how the dialogue presents a relational model for spiritual transformation that challenges traditional individualistic soteriological frameworks. The findings suggest that friendship-based approaches to mission and pastoral care are more effective in pluralistic contexts, offering practical implications for contemporary evangelism, discipleship, and interfaith engagement. This research contributes to Johannine scholarship by highlighting previously under-explored relational dimensions of the Fourth Gospel's theology.   Abstrak Penelitian ini mengkaji dialog antara Yesus dan Nikodemus dalam Yohanes 3:1-21 melalui lensa teologis persahabatan, menawarkan perspektif baru terhadap narasi Injil yang sangat penting ini. Menggunakan hermeneutika naratif yang dikombinasikan dengan analisis teologi biblikal, penelitian ini mendemonstrasikan bahwa persahabatan berfungsi bukan hanya sebagai kategori antropologis tetapi sebagai konsep teologis fundamental untuk memahami misi, soteriologi, dan eklesiologi. Analisis mengungkapkan bahwa pendekatan Yesus kepada Nikodemus mewujudkan karakteristik persahabatan yang autentik: pengakuan, keterlibatan intelektual, rasa hormat mutual, dan komitmen transformatif. Berdasarkan teologi persahabatan kontemporer, khususnya konsep "persahabatan terbuka" Jürgen Moltmann, studi ini menunjukkan bagaimana dialog tersebut menyajikan model relasional untuk transformasi spiritual yang menantang kerangka soteriologis individualistik tradisional. Temuan menunjukkan bahwa pendekatan berbasis persahabatan dalam misi dan pelayanan pastoral lebih efektif dalam konteks pluralistik, memberikan implikasi praktis untuk evangelisme, pemuridan, dan keterlibatan antaragama kontemporer.